2022
DOI: 10.1371/journal.pone.0276194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of visual impairment among adult diabetic patients visiting Adare General Hospital, Hawassa, South Ethiopia, 2022

Abstract: Background The increased prevalence of visual impairment among diabetic patients has become a major public health problem. However, there was limited information on the extent of visual impairment among diabetic patients in our country, and there was no study in the study area. Providing updated data regarding this area is critical for the prevention of visual impairment among diabetic patients. Purpose The study aimed to assess the prevalence and associated factors of visual impairment among adult diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…treatment. As a result, glucose levels in the blood vessels will increase to exacerbate the development of PDR [41]. This result was in line with the study conducted in Malaysia [17].…”
Section: Plos Onesupporting
confidence: 87%
“…treatment. As a result, glucose levels in the blood vessels will increase to exacerbate the development of PDR [41]. This result was in line with the study conducted in Malaysia [17].…”
Section: Plos Onesupporting
confidence: 87%
“…In addition, those who regularly exercise were found to have lower odds of having DR than those who do not exercise regularly. This nding is supported by studies done in Addis Ababa [11] , Hawassa [29], and Dessie Ethiopia [30] that showed lower odds of having DR among patients with diabetes who had exercise self-care. However, a study done in china did not show a statistically signi cant association between exercise and diabetic retinopathy [31].…”
Section: Discussionmentioning
confidence: 54%
“…Following the additional screening, eighteen articles were evaluated for eligibility, with three being excluded due to being incomplete, of poor quality, or not in full text ( Fig 1 ). Finally, fifteen studies were reviewed for co-morbid HTN [ 21 – 35 ] ( Table 2 ), six studies for poor glycemic control [ 21 , 22 , 24 , 25 , 28 , 32 ] ( Table 3 ), and five studies for the duration of diabetic illness [ 21 , 22 , 25 , 27 , 31 ] ( Table 4 ). Of the total studies; five were conducted in the Amhara region [ 21 , 23 , 27 , 30 , 34 ], five in Addis Ababa [ 24 , 26 , 29 , 32 , 35 ], three in the Oromia region [ 25 , 31 , 33 ], and two in South Nations and Nationalities people (SNNP) of Ethiopia [ 22 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, fifteen studies were reviewed for co-morbid HTN [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2), six studies for poor glycemic control [21,22,24,25,28,32] (Table 3), and five studies for the duration of diabetic illness [21,22,25,27,31] (Table 4). Of the total studies; five were conducted in the Amhara region [21,23,27,30,34], five in Addis Ababa [24,26,29,32,35], three in the Oromia region [25,31,33], and two in South Nations and Nationalities people (SNNP) of Ethiopia [22,28].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%